Teachers’ Multiple Roles and Work Attitude: A Gender-Wise Comparison at Secondary Level School - Afsheen Gul; Ayesha Ahmad Khan; Fatima Afzal; Rabia; Haseena Gul, (Dialogue Social Science Review (DSSR), 2025)
This study focused on the investigation of the teachers’ multiple roles and its effects on their work attitude at secondary school level of District Mardan. The objectives of the study were to examine the relationship of multiple role and work attitude of the teacher, gender-wise and to find out the association of one role of a teacher with specific work attitude. The study was qualitative in nature. Two questionnaires were designed by the researcher, one for multiple roles and the second questionnaire was for Work attitude. The questionnaires were distributed among subject specialists and senior school teachers of district Mardan. The collected data was analyzed through SPSS Version 16.0. The data was analyzed through mean score, standard deviation and Pearson correlation. The result revealed that the total mean score of multiple roles was120.11 and STD was 8.089 while the total mean score for attitude was 110.60 and STD was 7.713 for male teachers. The correlation between multiple roles and attitude of male teachers was .301 which means that there is significant correlation and for female teachers it was found as .249 which also showed significant correlation.